Effect of Amazon Sword (Echinodorus grisebachii) Plant Density on Specific Growth Rate of Platy Fish (Xiphophorus maculatus) - Ardiansyah Ardiansyah; Felix Rebhung; Yudiana Jasmanindar (Advances in Tropical Biodiversity and Environmental Sciences, 2024)
This study aimed to determine the effect of Amazon sword plant density on the specific growth rate of platyfish. The research during April-May was carried out in the dry land lab of the Semiri islands, University of Nusa Cendana. Platy fish that use as many as 120 tails. The research method used a completely randomized design with four treatments and 3 replications. Control treatment (without plants; treatment A (using three root plants), treatment B (using five root plants), and treatment C (using seven root plants). The best treatment results were shown in treatment C with an absolute average weight value of 0. 35 g. ANOVA showed that the difference in the density of Amazon sword plants in rearing media affected platyfish's water quality and growth rate.